Kesulitan pemecahan masalah matematis siswa berdasarkan self-esteem pada materi statistika - Dini Kurniasari; Teni Sritresna (Jurnal Inovasi Pembelajaran Matematika: PowerMathEdu, 2022)
This study aims to determine the difficulties experienced by students in solving mathematical problems based on self-esteem in statistical material. The self-esteem of students with categories of high students, medium students, and low students. The research method used is descriptive qualitative. Data collection techniques in this study were the distribution of student self-esteem questionnaires, tests of students' mathematical problem-solving abilities, and interviews. This research was conducted in Kp. Ciloa Rt. 01 Rw. 08 Dec. Banjarsari district. Bayongbong Kab. Garut with the research subject of 3 students taken from class VIII and IX for the 2019/2020 academic year around Kp. Ciloa, the selected students were students in the high, medium, and low mathematical self-esteem categories. The subject matter used in this research is statistical material. The research instrument includes a student self-esteem questionnaire, questions about students' mathematical problem-solving abilities in the form of descriptions, and interviews. Based on the results of the study, it was found that students with high self-esteem categories in working on the problem-solving problems given did not experience difficulties and tended to understand concepts in mathematics, students with self-esteem categories were in the process of working on mathematical concepts and students with high self-esteem categories did not understand mathematical concepts. low self-esteem in the process, these students do not understand the concepts in mathematics so they are unable to work on the questions given by the researcher. Penelitian ini bertujuan untuk mengetahui kesulitan yang dialami siswa dalam pemecahan masalah matematis berdasarkan self-esteem pada materi statistika. Self-esteem siswa dengan kategori siswa tinggi, siswa sedang dan siswa rendah. Metode penelitian yang digunakan adalah kualitatif deskriptif. Teknik pengumpulan data dalam penelitian ini adalah penyebaran angket self-esteem siswa, tes kemampuan pemecahan masalah matematis siswa dan wawancara. Penelitian ini dilaksanakan di Kp. Ciloa Rt. 01 Rw. 08 Des. Banjarsari Kec. Bayongbong Kab. Garut dengan subjek penelitian 3 orang peserta didik yang diambil dari kelas VIII dan IX tahun ajaran 2019/2020 yang ada disekitar Kp. Ciloa, peserta didik yang terpilih adalah peserta didik dalam kategori self esteem matematis tinggi, sedang dan rendah. Pokok bahasan yang digunakan dalam penelitian ini adalah materi statistika. Instrumen penelitian ini mencakup angket self-esteem siswa, soal-soal kemampuan pemecahan masalah matematis siswa yang berbentuk uraian dan wawancara. Berdasarkan hasil penelitian diperoleh bahwa siswa dengan kategori self-esteem tinggi dalam pengerjaan soal-soal pemecahan masalah yang diberikan tidak mengalami kesulitan dan cenderung memahami konsep dalam matematika, siswa dengan kategori self-esteem sedang dalam pengerjaannya siswa tersebut kurang memahami konsep matematika dan siswa dengan kategori self-esteem rendah dalam pengerjaannya siswa tersebut tidak memahami konsep dalam matematika sehingga tidak mampu mengerjakan soal yang diberikan oleh peneliti.